Public Response Regarding Health Risks Posed by Rats and Flies in Densely Populated Housing (HEALTH CARE: JURNAL KESEHATAN, 2025)
Dense settlements such as Perumnas Mandala in Medan have a high risk of spreading diseases caused by vector animals such as rats and flies. This study aims to determine the community's response to the health risks caused by vector animals and the factors that influence them. The study used a descriptive qualitative approach with in-depth interviews, observations, and documentation of 10 informants from various backgrounds. The results showed that some people have an understanding of the dangers of vector animals, but the preventive actions taken are still limited and tend to be reactive. Factors such as access to information, personal experience, and lack of education from the government influence people's behavior. Market traders are aware of the risks to health and the economy, but have not fully implemented good sanitation practices. The study concluded that there is a need for ongoing education, provision of environmental facilities, and active support from the government and health cadres to reduce the risk of vector-borne diseases